Modelagem e acionamento de diodos orgânicos emissores de luz (OLEDs) para sistemas de iluminação - Bender, Vitor Cristiano (2015)
This thesis presents the study and characterization of organic light-emitting diodes (OLEDs) with the proposal of obtaining an equivalent model that is useful in the OLED driver design and in lighting systems projects. Initially, a literature review covering the operating principle and the constructive aspects of OLEDs is presented. From this, a model that integrates scale, photometrical, electrical and thermal aspects is proposed. This model is static and dynamic and is called EFET. A procedure for parameter identification of the model is proposed, jointly with an analysis of the intrinsic capacitance effect on the OLED electrical, thermal and photometrical performance. The proposed model is able to predict and simulate the OLED based lighting systems before building, saving time and cost. The model is validated using different OLED samples and conclusions are derived from the experimental validation and simulation results. An approach considering the dimming methods of OLEDs is presented, showing the chromatic impact caused by each method. Finally, an OLED driver based on the concept of switched capacitor converters is proposed. The thesis results are satisfactory and provide an enhancement to the state of the art in modeling and OLED driving.